Fault size and depth extent of the Ecuador earthquake (Mw 7.8) of 16 April 2016 from teleseismic and tsunami data. Issue 5 (11th March 2017) - Heidarzadeh, Mohammad; Murotani, Satoko; Satake, Kenji; Takagawa, Tomohiro; Saito, Tatsuhiko
Abstract: The April 2016 Ecuador Mw 7.8 earthquake was the first megathrust tsunamigenic earthquake along the Ecuador‐Colombia subduction zone since 1979 ( Mw 8.2 with 200 deaths from tsunami). While there was no tsunami damage from the 2016 earthquake, small tsunamis were recorded at Deep‐ocean Assessment and Reporting of Tsunami and tide gauges. Here we designed various fault models with and without shallow‐slip area and compared the computed teleseismic and tsunami waveforms with the observations. While teleseismic inversions were indifferent about inclusion or exclusion of the shallow slip, tsunami waveforms strongly favored the slip model without shallow slip. Our final slip model has a depth range of 15–44 km, and its western shallowest limit is located at the distance of ~60 km from the trench. Maximum and average slips were 2.5 and 0.7 m, respectively. The large‐slip area was 80 km (along strike) × 60 km (along dip) in the depth range of 15–35 km. Key Points: The 2016 Ecuador earthquake ( Mw 7.8) is similar to the 1942 event ( Mw 7.8) which was followed by 1958 ( Mw 7.7) and 1979 ( Mw 8.2) events While teleseismic inversion was neutral about inclusion or exclusion of slip shallower than 15 km, observed tsunamis favored the latter Final fault had a maximum slip of 2.5 m and a large‐slip area of 80 km (strike wise) times 60 km (dip wise) in the depth range of 15–35 km